2017
DOI: 10.1161/circgenetics.116.001671
|View full text |Cite
|
Sign up to set email alerts
|

Burden of Recurrent and Ancestral Mutations in Families With Hypertrophic Cardiomyopathy

Abstract: Background-Hypertrophic cardiomyopathy is a genetically heterogeneous myocardial disease with >1000 causal variants identified. Nonunique variants account for disease in many families. We sought to characterize nonunique variants in Australian families and determine whether they arise from common ancestral mutations or recurrent mutation events.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
9
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(9 citation statements)
references
References 34 publications
0
9
0
Order By: Relevance
“…In other well-established HCM genes 76% of variants were unique. 93 The corollary of the above is that if the VUS does not segregate with affected family members, the likelihood that the VUS is relevant for the family phenotype is reduced. However, this analysis must encompass the growing reality of bilineal or multivariant disease, which has been postulated to be more common in DCM 9,56 and ARVC.…”
Section: Positive Cascade Genetic Testing In An At-risk Family Membermentioning
confidence: 99%
“…In other well-established HCM genes 76% of variants were unique. 93 The corollary of the above is that if the VUS does not segregate with affected family members, the likelihood that the VUS is relevant for the family phenotype is reduced. However, this analysis must encompass the growing reality of bilineal or multivariant disease, which has been postulated to be more common in DCM 9,56 and ARVC.…”
Section: Positive Cascade Genetic Testing In An At-risk Family Membermentioning
confidence: 99%
“… 8 , 9 However, this approach needs to be used with caution as variants that are not very rare, including founder and recurrent variants, have been reported in HCM. 10 Previous studies identified 2 founder variants of MYBPC3 that are significantly enriched in HCM cases in South Asian 11 and Icelandic populations, 12 which are now mostly classified as pathogenic by clinical genetics laboratories in ClinVar despite being relatively common in specific populations. It is important to have a firm understanding of the genetic architecture of HCM in a given population, and to recognize population-specific alleles, including founder variants, before the ACMG/AMP framework can be confidently applied in that population.…”
mentioning
confidence: 99%
“…We observed a high rate of recurrent P (67.8%) and LP variants that were present in more than 2 unrelated subjects, results that are in line with those reported for large cohorts. 24,26,27 MYBPC3 and MYH7 are commonly reported as the 2 most prevalent HCM-related genes in Caucasian and some non-Caucasian populations. 26,28,29 The highest prevalence of MYBPC3 mutations observed in this study was consistent with previous reports.…”
Section: Discussionmentioning
confidence: 99%